Rastreamento sorológico da infecção pelo vírus da hepatite C em cortadores de cana-de-açúcar nos estados de Goiás e Paraíba - Oliveira, Brunna Rodrigues de (2019)
Introduction: Hepatitis C virus (HCV) infection is a major problem for a global public health, with about 71 million people chronically infected worldwide, being a major cause of cirrhosis and hepatocarcinoma. The World Health Organization (WHO) set the goal of eliminating viral hepatitis as a public health problem by 2030. To do so, it is necessary to track infections in all populations. Sugarcane cutters are a population of seasonal workers, with difficulty to access to health services, which lack information on hepatitis C. Objective: This study aimed to perform the serological screening of hepatitis C virus infection in sugarcane cutters in Goiás and Paraíba. Methods: The population consisted of 937 sugar cane cutters, 636 in Goiás and 301 in Santa Rita-PB. All cutters were invited to participate in the study, and those who signed the consent form were interviewed using a standardized questionnaire. Then, blood samples were collected and screened for anti-HCV by rapid tests and ELISA. The data were analyzed in the statistical program SPSS version 17.0 for Windows. Results: The population was composed of males (100%), with a mean age of 35.4 years. Regarding schooling, 47.4% reported having up to four years of study and the monthly family income of 78.8% of the participants was less than 2,000.00 reais. After screening for anti-HCV by rapid test and ELISA, it was verified that no individual was exposed to HCV. The risk characteristics for potential viral spread reported by cane cutters were tattooing/piercing, sharing of personal use material, and use of non-injectable drugs. Rapid tests are highly sensitive to anti-HCV, so they are appropriate and feasible for hard-to-reach populations such as sugarcane cutters and other populations. Conclusion: The present study showed that there was no exposure to HCV in the sugarcane cutters of the regions of Goiás and Santa Rita-PB. To achieve WHO's goal of eliminating viral hepatitis as a public health problem, it is important that more research on HCV prevalence is conducted, especially in groups that have difficulty accessing the health system.